ERP systems selection in multinational enterprises: a practical guide - Haddara, Moutaz (2022)
The Enterprise Resource Planning (ERP) system selection is an early phase in the ERP adoption process. When organizations evaluate an ERP, they commonly develop their own selection criteria that usually involve various system and vendor related factors. While the selection process is critical, however, there is an apparent research gap in literature. The ERP selection effort also focuses on the system’s fit with the organizational requirements and needs. Thus, the selection phase is critical, because if an organization chooses an unfit ERP, the whole project could be predestined to fail. This research provides an overview of an ERP selection process at an overseas branch office of a multinational company. The process employed a simple multi-attribute rating technique (SMART) for evaluation. In addition, this research presents how cross-border data protection laws between the parent company and its branch have influenced the selection process. As the ERP system has been implemented successfully, the method and the selection factors have been proven adequate for the selection process.